FAKTOR-FAKTOR YANG MEMPENGARUHI PERUBAHAN DALAM TATA CARA PERKAWINAN ADAT BATAK SIMALUNGUN DI NAGORI SERBELAWAN KECAMATAN DOLOK BATU NANGGAR KABUPATEN SIMALUNGUN PROVINSI SUMATERA UTARA - Situmorang, Eka Erlia; Hambali, Hambali; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by a change in the procedure of Batak Simalungun traditional marriage in Nagori Serbelawan, Dolok Batu Nanggar District, Simalungun Regency, North Sumatra Province. The formulation of the problem is (1) What aspects have changed in the Simalungun Batak customary marriage procedures in Dolok Batu Nanggar District, Simalungun Regency, North Sumatra Province. (2) What factors influence changes in the customs of the Batak Simalungun traditional marriage of Dolok Batu Nanggar District, Simalungun Regency, North Sumatra Province. Research Objectives (1) To find out what aspects have changed in the Simalungun Batak customary marriage procedures in Dolok Batu Nanggar District, Simalungun Regency, North Sumatra Province. (2) To find out what factors influence changes in the customary marriage procedures of the Batak Simalungun District, Dolok Batu Nanggar District, Simalungun Regency, North Sumatra Province.This research is descriptive qualitative. Data collection techniques in this study are, observation, interviews, documentation. There were 10 informants in this study, the determination of the informants was done by using purposive sampling. The results of this study indicate that there are aspects that have changed in the procedure of Batak Simalungun adat marriage in Dolok Batu Nanggar District, Simalungun Regency, North Sumatra Province.In this study the factors that influence change are internal factors such as discovery (new discovery) and invention (application of new discoveries). In addition it is also influenced by external factors such as diffusion and acculturation.Key Words : Factors, Change, Marriage, Simalungun Batak